Reliable user datagram protocol (RUDP). - Thammadi, Abhilash (Kansas State University, 2011)
As the network bandwidth and delay increase, TCP becomes inefficient. Data intensive applications over high-speed networks need new transport protocol to support them. This project describes a general purpose high performance data transfer protocol as an application level solution. The protocol Reliable UDP-based data transfer works above UDP with reliability. Reliable Data Transfer protocol provides reliability to applications using the Sliding Window protocol (Selective Repeat). UDP uses a simple transmission model without implicit handshaking techniques for providing reliability and ordering of packets. Thus, UDP provides an unreliable service and datagrams may arrive out of order, appear duplicated, or go missing without notice. Reliable UDP uses both positive acknowledgements and negative acknowledgements to guarantee data reliability. Both simulation and implementation results have shown that Reliable UDP provides reliable data transfer. This report will describe the details of Reliable UDP protocol with simulation and implementation results and analysis.
Keywords: Sliding window protocol; Reliable UDP; Computer Science (0984)